2011
DOI: 10.1016/j.vascn.2010.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of metals on β-actin and total protein synthesis in cultured human intestinal epithelial cells

Abstract: As an important structural protein, β-actin is associated with anchoring of tight junctions (TJs) to the cell scaffold. Caco-2 cells, an immortal intestinal epithelial cell line, rely on β-actin to form intact monolayers with high transepithelial electrical resistance in cell culture inserts. We examined the effect of six metals on expression of β-actin mRNA and β-actin synthesis, on total and net production of newly synthesized proteins, on paracellular transport of TJ markers, and on cell viability in conflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
1
7
0
1
Order By: Relevance
“…These findings are also in agreement with studies in epithelia other than the testis, such as the small intestine, kidney, liver, and skin, which imply that cell junctions are the target of different classes of reproductive toxicants, including cadmium (Fiorini et al, 2004;Zefferino et al, 2008;Pinton et al, 2009;Choi et al, 2010;Li et al, 2010). In addition, there is mounting evidence that both AJ (and/or TJ) (Prozialeck and Lamar, 1999;Prozialeck, 2000;Prozialeck et al, 2003;Jacquillet et al, 2007;Thompson et al, 2008;Siu et al, 2009b,c;Calabro et al, 2011) and gap junction (Fukumoto et al, 2001;Jeon et al, 2001;Guan et al, 2007;Tang et al, 2009;Vinken et al, 2010) are targets of cadmium toxicity in multiple epithelia in different organs, such as the kidney, heart, liver, ovary, and testis.…”
Section: Cellular Targets Of Cadmium In the Testissupporting
confidence: 87%
“…These findings are also in agreement with studies in epithelia other than the testis, such as the small intestine, kidney, liver, and skin, which imply that cell junctions are the target of different classes of reproductive toxicants, including cadmium (Fiorini et al, 2004;Zefferino et al, 2008;Pinton et al, 2009;Choi et al, 2010;Li et al, 2010). In addition, there is mounting evidence that both AJ (and/or TJ) (Prozialeck and Lamar, 1999;Prozialeck, 2000;Prozialeck et al, 2003;Jacquillet et al, 2007;Thompson et al, 2008;Siu et al, 2009b,c;Calabro et al, 2011) and gap junction (Fukumoto et al, 2001;Jeon et al, 2001;Guan et al, 2007;Tang et al, 2009;Vinken et al, 2010) are targets of cadmium toxicity in multiple epithelia in different organs, such as the kidney, heart, liver, ovary, and testis.…”
Section: Cellular Targets Of Cadmium In the Testissupporting
confidence: 87%
“…Researches have shown that, in mammals, mercury can induce a wide range of adverse effects on systems and tissues12345. Aplastic anemia is another potential consequence of inorganic mercury exposure6.…”
mentioning
confidence: 99%
“…The increasing awareness of the influence of growth factors (GFs) and basement membrane substrata has improved our understanding of the role of cell regeneration in wound repair and in preneoplastic tumor growth. For instance, in their ability to form tight junction (TJ) strands, differentiating epidermal and epithelial cells act to prevent free exchange of most solutes between luminal and interstitial fluids along the paracellular route (Calabro, Gazarian, and Barile, 2011). Breakdown in the barrier functions of these membranes may contribute to cellular neoplasia.…”
Section: Culture Of Stem Cellsmentioning
confidence: 99%